Amnesia: Definition, main models, classifications, neurobiological profiles and clinical treatments - Giulio Perrotta (Archives of Depression and Anxiety - Peertechz Publications, 2020)
This work focuses on the theme of amnesia and in particular on the clinical, psychopathological and neurophysiological elements. It is evident that the resolution of the amnestic condition depends mainly on the clinical cause that originates it and therefore on its management and recovery. Amnesia is therefore a symptom of a more extensive pathological condition, which must be investigated and treated with the best possible techniques, except for the hypotheses of irreparable damage.